A General Metal‐Assisted Synthesis of α‐Halo Oxime Ethers from Nitronates and Nitro Compounds. Issue 36 (19th November 2014) - Sukhorukov, Alexey Yu.; Kapatsyna, Maria A.; Yi, Tammy Lim Ting; Park, Hyeong Ryool; Naumovich, Yana A.; Zhmurov, Petr A.; Khomutova, Yulia A.; Ioffe, Sema L.; Tartakovsky, Vladimir A.
Abstract: An approach to the synthesis of α‐halo oxime ethers from readily accessible nitronates and nitro compounds via bis(oxy)enamines is reported. A key step of the strategy involves the unprecedented reaction of bis(oxy)enamines with a metal (Co, Zn, Mg, Mn) halide that acts as both a promoter and halide (Br, I, Cl) source. A variety of cyclic and acyclic ethers of α‐halo oximes, including previously unavailable trimethylsilyl ethers of α‐iodo oximes, have been synthesized in good‐to‐high yields. Abstract : A general approach to the synthesis of α‐halo oxime ethers is reported. The strategy involves as a key step an unprecedented reaction of readily accessible bis(oxy)enamines with a metal halide that acts both as a promoter and halide source. A variety of cyclic and acyclic ethers of α‐halo oximes have been synthesized in good‐to‐high yields.